Thermoplastic polyurethane-carbon black nanocomposite coating: Fabrication and solid particle erosion resistance - Dong, Mengyao; Li, Qiang; Liu, Hu; Liu, Chuntai; Wujcik, Evan K.; Shao, Qian; Ding, Tao; Mai, Xianmin; Shen, Changyu; Guo, Zhanhu (Polymer (Guilford), 2018)
Carbon black (CB)/thermoplastic polyurethane (TPU) nanocomposites with a range of nanoparticle loadings were prepared successfully by using a joint co-coagulation technique and hot pressing. The presence of hydrogen bonding interactions between the CB particles and TPU chains was identified from the results of Fourier transform infrared (FT-IR) spectroscopy and differential scanning calorimetry (DSC). Uniform dispersion of CB particles throughout the TPU matrix improved the overall mechanical properties of the TPU nanocomposites, as compared with the neat TPU. The thermal conductivity and thermal stability of the CB/TPU nanocomposites were also found to be enhanced with increasing the CB loading. All samples exhibited a rapid increase of erosion rate with the impact velocity between 20 and 30 m/s. The largest and smallest erosion rates (ER) were observed at 30° and 90° impact angle, respectively, for all CB/TPU nanocomposites. This shows a typical ductile erosion behavior in this material. In addition, the ER (TPU-2CB > TPU-12CB > TPU > TPU-6CB) under all test conditions showed an opposite trend to the tensile strength. These results indicate that the CB/TPU nanocomposites are suitable for protective coatings. [Display omitted] •Thermoplastic polyurethane nanocomposites were fabricated using co-coagulation plus compression molding technique.•Uniform dispersion of CB nanoparticles effectively enhanced the tensile strength of the nanocomposites.•The solid particle erosion behavior was characterized by different impact angles, velocities and time.•The erosion rate showed an opposite trend to the tensile strength.